ANALISIS PEMIKIRAN MUHAMMADIYAH DALAM PERSPEKTIF SALAFISME - Ciptadi, Muhammad Teguh; Romelah, Romelah; Nurhakim, Moh. (Jurnal Hadratul Madaniyah, 2024)
Muhammadiyah as an open and moderate organization, easily accepts ideas and actions from other Islamic groups that have ideologies similar to Muhammadiyah. One such movement is Salafism. The introduction of Salafism into Muhammadiyah has caused various reactions, especially among the Muslims themselves. Some of the issues faced include how the Salafi movement affects the citizens of the Muhammadiyah association, whatever similarities and differences between Salafi and Muhammadiyah movements, as well as the impact of Salafi movements on the Mohammedan association. The research model uses qualitative, and in its discussion this research uses descriptive methods of analysis, while in obtaining data using library methods.In different perspectives, Muhammadiyah is often associated with Salafism and even the movement of radicalism. In addition, the young Mohammedan generation can be influenced by Islamic discourse and transnational movements such as salafism. Furthermore, the unrest that is occurring in Muslim-majority countries in various regions of the world can affect the thinking and attitudes of the young Mohammedan generation. The Muhammadiyah, who has struggled for more than a hundred years to encourage moderation and progress in Islam, is considered too great to change its moderate and progressive tradition, despite the challenges and temptations. The vision of Islamic progress and religious moderation in Indonesia will remain held by the Muhammadiyah.